2016
DOI: 10.1016/j.ijscr.2016.06.053
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of congenital intestinal malrotation in a nonagenarian

Abstract: HighlightsCongenital intestinal malrotation can go undiagnosed late in life and as late as into 90 years of age.CT imaging is necessary for diagnosed yet can be misleading in the presence of other ongoing pathologies.Lactic Acidosis and peritonitis in the setting of malrotation are a surgical emergency.Careful and thorough review with awareness of “classic” radiographic signs of malrotation are important for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…5,15 Fernandez-Moure et al however in a case report described a nonagenarian with acute presentation and no history suggestive of chronicity similar to the patient we are reporting. 3 Similar presentation was also reported by Singh et al and Emanuwa et al 2,4 Other forms of presentation reported in literature include left sided acute appendicitis (a dicey conundrum for the general surgeon in the elderly) and caecal volvulus as reported by Chuang et al and Hanna and Akoh respectively. 10,19 In a review of literature of forty-nine patients found to have malrotation with colon cancer in Japan, Nakatani et al noted that about 69.4% of the patients were noted to have non-rotation anomalies and diagnosis was made by as incidental findings during radiological investigations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…5,15 Fernandez-Moure et al however in a case report described a nonagenarian with acute presentation and no history suggestive of chronicity similar to the patient we are reporting. 3 Similar presentation was also reported by Singh et al and Emanuwa et al 2,4 Other forms of presentation reported in literature include left sided acute appendicitis (a dicey conundrum for the general surgeon in the elderly) and caecal volvulus as reported by Chuang et al and Hanna and Akoh respectively. 10,19 In a review of literature of forty-nine patients found to have malrotation with colon cancer in Japan, Nakatani et al noted that about 69.4% of the patients were noted to have non-rotation anomalies and diagnosis was made by as incidental findings during radiological investigations.…”
Section: Discussionsupporting
confidence: 79%
“…Midgut volvulus secondary to intestinal malrotation is a rare condition in the elderly with very few cases reported in literature. 3,[5][6][7][8][9][10][11][12][13][14] The first case in the elderly was probably reported in 1992 by Izes et al at the Lahey Clinic Medical Centre, USA. 15 Its rarity therefore portends a challenge in diagnosis and this mostly dependent on a high index of suspicion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations